Аэродинамический расчет и усовершенствование турбомашин с помощью решателя FlowER - Ершов, С. В. (Eastern-European Journal of Enterprise Technologies, 2009)
By the example of solver FlowER, the questions of flow modelling, turbulence modelling and numerical technique are discussed. Numerical results are presented for turbomachinery flows including unsteady effects, leakages, film cooling and optimization of blade shape